Peran Dikmas Lantas dalam Melakukan Pelayanan SIM Online kepada Publik di Polres Tasikmalaya - Satria Bimantara Burhan (Advances in Police Science Research Journal, 2019)
In this day and age modernization has brought great influence to the countries in the world, one of which is Indonesia, modernization is very closely related to society, especially developments in technology. The Unit Then the unit is assumed to have a role in the effort to socialize the online sim program with the community education then. This study aims to analyze and describe the efforts and factors that influence the implementation of the task of community education and then on sim online. The location of the study was at the Tasikmalaya Regional Police with the focus of the Dikmas Lantas Dikyasa unit. This study uses qualitative methods with descriptive analysis techniques. Using data triangulation (Moleong; 2006: 330) 4 (four) kinds of techniques namely sources, theories and techniques as well as primary, secondary and tertiary data sources. Data validity is data reduction, data display, conclusion drawing and verification. This research uses management theory, communication theory and swot analysis theory as well as the concept of community education then, and the concept of service. The implementation of sub-optimal services performed by the units is assumed to be analyzed from the planning function, namely the preparation of material not in written form such as brochures, banners and brochures, organizing, namely preparing officers who are maximum in quality and quantity, implementation that does not show video and control, namely monitoring in extension activities. In the implementation of services there are internal factors that influence are the factors of people, infrastructure and counseling methods and external factors that influence are economic factors and public knowledge. The conclusion is that binluh inhibiting factors carried out by the bintibmas unit are member competencies, extension materials, budgets, cooperation with other functions and agencies, binluh target determination and binluh methods.